Treating Systemic Juvenile Idiopathic Arthritis with Tocilizumab: Clinical Case - E. I. Alekseeva; S. I. Valieva; T. M. Bzarova; R. V. Denisova; T. V. Sleptsova; O. L. Lomakina; A. M. Chomakhidze (Union of pediatricians of Russia, 2016)
This article describes a case of successfully used tocilizumab (interleukin 6 receptors monoclonal antibodies) in a two-year patient with severe systemic juvenile idiopathic arthritis resistant to oral and parenteral glucocorticoids, nonsteroidal anti-inflammatory drugs, and methotrexate. Just after the first injection of tocilizumab, fever and pain ceased, morning stiffness decreased significantly; laboratory disease activity indices normalized by the 4th week of drug use; by the 16th week inflammatory changes in the joints regressed completely, the disease entered its inactive phase. After using tocilizumab, remission duration was 20 months for articular syndrome and systemic manifestations. No adverse reactions have been registered.